2020
DOI: 10.1101/2020.02.14.949289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SPRTN protease and SUMOylation coordinate DNA-protein crosslink repair to prevent genome instability

Abstract: max 150 words) DNA-protein crosslinks (DPCs) are a specific type of DNA lesions where proteins are covalently attached to DNA. Unrepaired DPCs lead to genomic instability, cancer, neurodegeneration and accelerated ageing. DPC proteolysis was recently discovered as a specialised pathway for DPC repair. The DNA-dependent SPRTN protease and 26S proteasome emerged as as two independent proteolytic systems for DPC repair. DPCs are also repaired by homologous recombination (HR), a canonical DNA repair pathway. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Emerging evidence suggests that SUMO controls the SprT family of proteases in higher eukaryotes. Although the Wss1 ortholog SPRTN lacks an obvious SIM domain, a recent preprint nevertheless reported that SUMO stimulates its proteolytic activity ( Vaz et al, 2020 ). Another Wss1 ortholog, GCNA, has a SUMO-binding domain and is targeted to DPC sites in a SUMO-dependent manner ( Borgermann et al, 2019 ; Dokshin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that SUMO controls the SprT family of proteases in higher eukaryotes. Although the Wss1 ortholog SPRTN lacks an obvious SIM domain, a recent preprint nevertheless reported that SUMO stimulates its proteolytic activity ( Vaz et al, 2020 ). Another Wss1 ortholog, GCNA, has a SUMO-binding domain and is targeted to DPC sites in a SUMO-dependent manner ( Borgermann et al, 2019 ; Dokshin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently DNA-activated proteases ( 6 ) and the proteasome have been suggested to be involved in proteolysis by cleaving large DNA–protein cross-links to DNA–peptide cross-links ( 18 , 29 , 30 ). Some DNA-dependent proteases bind to ubiquitin, or small ubiquitin-like modifier (SUMO), indicative of a role for posttranslational modification in proteolysis ( 31 , 32 , 33 ). Ubiquitination is a key step for proteolysis by the nuclear DNA-dependent metalloprotease SPRTN ( 18 ).…”
mentioning
confidence: 99%
“…It is now known that SUMOylation of TOP2 by the ZATT E3 ligase facilitates the direct removal of TOP2-DNA covalent complexes by TDP2, as discussed above (Schellenberg et al, 2017). However, SUMO is also implicated in other relevant pathways which may affect TOP2-DNA covalent complex processing and repair, such as the SPRTN-dependent pathway (Vaz et al, 2020) and the recently described RNF4/ubiquitin-dependent proteasomal pathway. Following the SUMOylation of TOP2 by the E3 SUMO ligase PIAS4, RNF4 is recruited to TOP2 via its SIM domain and polyubiquitinates TOP2 with K48-linked chains, thereby leading to degradation of TOP2 by the proteasome (Sun et al, 2019).…”
Section: Sumoylation In Top2-dna Covalent Complex Repairmentioning
confidence: 98%